2021
DOI: 10.35860/iarej.832439
|View full text |Cite
|
Sign up to set email alerts
|

A novel formula derived by using ABC algorithm for calculation of the average fiber diameter of electrospun poly (Ԑ-caprolactone) scaffolds

Abstract: The characteristics of a scaffold that is the basic component of tissue engineering are considerably influenced by the fiber diameter of the fibrous scaffolds. Since the significant effect of the fiber diameter on the scaffold properties, many researchers have focused on estimating the fiber diameter based on the electrospinning parameters. With similar motivation, in this paper, a new and simple closed-form expression, which can help researchers in fabricating the electrospun poly (ԑ-caprolactone) (PCL) scaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…PCL nanofibers was manufactured using electrospinning technique according to method described in our previous studies (Fig. 1 ) 19 , 25 . Various process (tip-to-collector distance, voltage and flow rate) and solution parameters (polymer concentration, viscosity and conductivity) play a role in the formation of fiber structures of different morphologies 50 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCL nanofibers was manufactured using electrospinning technique according to method described in our previous studies (Fig. 1 ) 19 , 25 . Various process (tip-to-collector distance, voltage and flow rate) and solution parameters (polymer concentration, viscosity and conductivity) play a role in the formation of fiber structures of different morphologies 50 .…”
Section: Resultsmentioning
confidence: 99%
“…The experimental conditions selected for PCL nanofibrous scaffolds with different fiber diameters were determined by using the experimental sets created by response surface methodology in another study we previously reported 25 . Briefly, a polymer solution was prepared by dissolving the calculated amount of PCL in a solvent mixture containing 30:70 volumetric ratio of chloroform and dimethylformamide, respectively under continuous stirring for at least 120 min.…”
Section: Methodsmentioning
confidence: 99%